Features Analysis of Lower Extremity Arterial Lesions in 162 Diabetes Patients - XiangJiang Guo; YaXue Shi; XiaoZhong Huang; Meng Ye; GuanHua Xue; JiWei Zhang (Journal of Diabetes Research)
Objective. This study aimed to investigate the angiographic manifestations of lower extremity atherosclerotic steno-occlusive disease in patients with diabetes. Materials and Methods. A total of 162 patients with diabetes were enrolled in this study. The angiographic findings of lower extremity arterial lesions were evaluated according to location (iliac, femoral, popliteal, and crural artery), type (stenosis or occlusion), and length (<5 cm, 5–10 cm, and >5 cm). Results. A total of 131 of 162 (80.9%) diabetics showed multiple segmental lesions, and 19.1% (31/162) presented single segmental lesions in the lower extremity artery. Crural artery was the mainly involved location (39/162, 85.8%). Among the recorded 660 lesions of 162 cases, 437 (66.2%) were occlusion lesions, while 223 (33.8%) were stenosis lesions. Of 437 occlusion lesions, 308 lesions (70.5%) were in crural artery. More than 10 cm occlusion lesion (242/392, 61.7%) was the main manifestation in crural artery, especially in anterior (92/127, 67.2%) and posterior tibial arteries (91/124, 73.4%), which was higher than that in iliac artery (8/33, 24.2%), popliteal artery (53/157, 33.8%), and femoral artery (11/78, 14.1%). Conclusion. In diabetic subjects with lower limb artery ischemia, the vascular involvement is extremely diffuse and particularly severe in crural arteries, with high prevalence of more than 10 cm occlusion lesions.